Cerebral Amyloid Angiopathy- Related Inflammation: A Case Report and Literature Review - Chanjin Park; Eun Sun Choi; Eunhee Kim (Journal of the Korean Society of Radiology, 2023)
Cerebral amyloid angiopathy-related inflammation (CAA-RI) is an encephalopathy caused by inflammation of β-amyloid peptide deposition in cerebrovascular vessels. It is a rare disease that mainly occurs in the elderly and is characterized by rapidly progressive dementia, headache, seizures, and focal neurologic deficits. CAA-RI can demonstrate characteristic brain MRI findings and can be reversed by steroids or other immunosuppressive therapies. Here, we report a case of CAA-RI, which was initially misdiagnosed as a subacute infarction but was diagnosed while reviewing follow-up brain MRI images, and spontaneous remission was achieved.